Praktyka udostępnienia informacji publicznej - kwestie sporne - Jabłoński, Mariusz; Jarosz-Żukowska, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The study focuses on several specific issues. The first of them relates to the availability of public information based on the regulations concerning access to public information. The second is associated with an analysis of restrictions in the access to documents held by the obliged party with due account taken of the scope of protection ensured by specific regulations. In this respect, the article analyses the provisions of the Act of 16 February 2007 on Competition and Consumer Protection concerning the provision of access to public information in the course of investigations carried out pursuant to Article 481 and 2.
Keywords: informacja publiczna; udostepnianie informacji publicznej; ustawa o ochronie konkurencji i konsumentów - art. 481 i 2